2023
DOI: 10.3389/fphar.2023.1136321
|View full text |Cite
|
Sign up to set email alerts
|

Omics data integration facilitates target selection for new antiparasitic drugs against TriTryp infections

Abstract: Introduction:Trypanosoma cruzi, Trypanosoma brucei, and Leishmania spp., commonly referred to as TriTryps, are a group of protozoan parasites that cause important human diseases affecting millions of people belonging to the most vulnerable populations worldwide. Current treatments have limited efficiencies and can cause serious side effects, so there is an urgent need to develop new control strategies. Presently, the identification and prioritization of appropriate targets can be aided by integrative genomic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 108 publications
0
4
0
Order By: Relevance
“… 63 Furthermore, other authors have conducted a genome-wide multidimensional data integration strategy including genomic, transcriptomic, metabolic, and protein structural data sources, to identify candidate proteins with relevant features for target selection in drug development against Trypanosoma cruzi , Trypanosoma brucei , and Leishmania spp , which gave rise to a list of 319 common candidates. 64 Other similar approaches have also been described in the past few years. 65 , 66 …”
Section: Multiomics Aproachesmentioning
confidence: 97%
See 1 more Smart Citation
“… 63 Furthermore, other authors have conducted a genome-wide multidimensional data integration strategy including genomic, transcriptomic, metabolic, and protein structural data sources, to identify candidate proteins with relevant features for target selection in drug development against Trypanosoma cruzi , Trypanosoma brucei , and Leishmania spp , which gave rise to a list of 319 common candidates. 64 Other similar approaches have also been described in the past few years. 65 , 66 …”
Section: Multiomics Aproachesmentioning
confidence: 97%
“…For instance, a transcriptomic analysis of benznidazole-resistant and susceptible Trypanosoma cruzi populations was performed, generating a robust set of transcripts involved in different metabolic pathways associated with the benznidazole-resistant phenotype of the parasite, which is of utmost importance, since benznidazole is one of the two drugs currently approved for the treatment of the disease . Furthermore, other authors have conducted a genome-wide multidimensional data integration strategy including genomic, transcriptomic, metabolic, and protein structural data sources, to identify candidate proteins with relevant features for target selection in drug development against Trypanosoma cruzi, Trypanosoma brucei, and Leishmania spp , which gave rise to a list of 319 common candidates . Other similar approaches have also been described in the past few years. , …”
Section: Multiomics Aproachesmentioning
confidence: 99%
“…The efforts to find new drug targets against trypanosome infections are advancing, notably interference with the trypanothione metabolism pathway [142], calcium homeostasis, nucleoside analog targeting purine salvage pathway, and drug combination of low-cost molecules in T. cruzi [143,144]. Furthermore, it is now possible to perform in silico analysis to identify new drug targets in trypanosomes [14,145]. Several new molecular targets eligible for clinical trials have been identified [6].…”
Section: Control and Eradication Strategies For Trypanosoma Infectionsmentioning
confidence: 99%
“…Thus, high-throughput drug target identification using RNA interference is currently advancing [12]. Furthermore, integrative genomic and bioinformatics mining is possible, and can be used to facilitate target selection for new anti-Trypanosoma activities [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%